Distinct clinical characteristics of atypical optic neuritis with seronegative aquaporin-4 antibody among Chinese patients. Issue 12 (12th April 2017) - Zhou, Huanfen; Xu, Quangang; Zhao, Shuo; Wang, Wei; Wang, Junqing; Chen, Zhiye; Lin, Dahe; Li, Xiaoming; Peng, Chunxia; Ai, Nanping; Wei, Shihui
Abstract : Objective: To evaluate the clinical features and prognosis of atypical optic neuritis (ON) with seronegative aquaporin-4 (AQP4) antibody in Chinese patients. Methods: All patients with first or relapsing ON were recruited from the Neuro-ophthalmology Department of the Chinese People's Liberation Army General Hospital from January 2013 to December 2014 and assigned to one of three groups based on diagnosis: atypical ON, typical ON and neuromyelitis optica spectrum disorder (NMOSD)-ON. Results: A total of 173 patients were included in the cohort. Fifty patients (28.9%) were AQP4-Ab-positive and diagnosed with NMOSD-ON. Of 123 patients with seronegative AQP4-Ab, 37 (30.1%) patients had atypical ON, with male predominance (25, 67.6%). The atypical ON group (compared with the typical ON and NMOSD-ON groups) had a significantly lower female:male ratio (1:2.1 vs 1.8:1 and 9:1, respectively, p=0.001 and p<0.001), an older mean age of onset (44.8, 13–71 years vs 36.9, 13–73 years and 36.2, 13–66 years, p=0.003 and p=0.004), a lower rate of good (≥0.5) visual recovery (6.7% vs 79.8% and 30.9%, p<0.001 and p<0.001) and (compared with the NMOSD-ON group) a lower recurrence rate during a 2-year follow-up (29.3% vs 60%, p=0.009). However, none developed to multiple sclerosis or neuromyelitis optica in the atypical ON group. Conclusions: Atypical ON with seronegative AQP4-Ab had unique clinical features in this Chinese cohort, including male predominance, an older age of onset, worse visual acuity recovery and resistance to corticosteroid therapy. This condition may be a distinct nosological entity with an unusual clinical and therapeutic profile.